From genome assembly to functional interpretation: an epistemological shift in understanding plant mitochondrial architecture - Wang, Tianchao; He, Hao; Sun, Jinwei; Man, Jie; Li, Jiawei; Sun, Chaohua; Zhao, Yanjie; Kuang, Zheng; Liu, Yifei; Huang, Zhenyu; Zhao, Yongxin (Frontiers in Plant Science, 2025)
The plant mitochondrial genome exhibits high complexity and structural diversity, which pose major challenges to its accurate assembly and in-depth interpretation. In recent years, the rapid advancement of sequencing technologies has driven the development of multiple assembly tools tailored for plant mitochondrial genomes. This review systematically summarizes recent progress in plant mitochondrial genome assembly, focusing on several representative computational tools, including GetOrganelle, GSAT, HIMT, PMAT, TIPPo, and PMAT2, and discusses their algorithmic principles, major advantages, and potential limitations. Furthermore, we highlight the methodological transition of mitochondrial genomics from traditional static sequence reconstruction to dynamic structural modeling. Finally, we outline future perspectives in data integration, standardization, and community benchmarking, which will collectively contribute to establishing a unified analytical framework for interpreting the complexity of plant mitochondrial genomes.